Guru Grantha Shahib: A Model for Interfaith Understanding in Today’s World (Philosophy and Progress, 2019)
Though all the religions of the world teach love, preach sympathy for others and encourage man to exercise utmost self-restraint and have most profoundly been a source of inspiration for the highest good of mankind, the world today is torn by conflicts, enmity and religious hatred. In this predicament, a lasting and peaceful society is impossible unless different faiths are understood in their proper perspectives. Therefore, it is necessary that people belonging to different faiths understand each other well. This necessitates a constant dialogue and effort to generate moral and hearty religious thinking. The advocates of all the religions of the world emphasize the importance of certain virtues and moral values. Only these can foster unity and cohesion of mankind. But the moral and religious values cannot be invoked by force. This can be achieved through the exchange of words, kind words, sincere words and loving words that can reach the deepest fathoms of the heart.Philosophy and Progress, Vol#61-62-; No#1-2; Jan-Dec 2017 P 1-14